Improving Employee Satisfaction and Performance through Motivation, Organizational Culture, and Employee Competency in Pekanbaru City Health Office - Yunia Sari; Sudarno; Nyoto; Suyono (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The purposes of this study are (1) to determine, test, and analyze the influence of motivation, organizational culture, and competence on job satisfaction and performance of Pekanbaru City Health Office employees. (2) To find out, test, and analyze the effect of employee job satisfaction on employee performance at the Pekanbaru City Health Office. In this study, the population was all employees of the Pekanbaru City Health Office, namely 99 employees (Health Service Data for 2020). The sample is part of the population members. The sampling technique used in this study used a saturated sample. The number of samples used in this study is all members of the population of the research object, as many as 99 respondents. The data collection technique used is the documentation of existing data in the agency and the distribution of questionnaires through the google form. The data analysis technique in this research uses descriptive analysis and SEM Structural Equation Analysis model with the help of Smart PLS software. The results of the study show that the increase in performance can increase is really influenced by high employee motivation. Organizational culture has no significant impact on employee job satisfaction at the Pekanbaru City Health Office. Employee competence is proven to have a positive impact on employee job satisfaction. Employee work motivation does not have a significant impact on employee performance. Employee work organizational culture does not have a significant impact on employee performance. Employee competence has a positive and significant impact on employee performance. Employee job satisfaction has a significant impact on employee performance.